Flow synthesis of oxadiazoles coupled with sequential in-line extraction and chromatography - Donnelly, Kian; Baumann, Marcus (Beilstein Journal of Organic Chemistry, 2022)
An efficient continuous flow process is reported for the synthesis of various 1,3,4-oxadiazoles via an iodine-mediated oxidative cyclisation approach. This entails the use of a heated packed-bed reactor filled with solid K2CO3 as a base. Using DMSO as solvent, this flow method generates the target heterocycles within short residence times of 10 minutes and in yields up to 93%. Scale-up of this flow process was achieved (34 mmol/h) and featured an integrated quenching and extraction step. Lastly, the use of an automated in-line chromatography system was exploited to realise a powerful flow platform for the generation of the heterocyclic targets.
Keywords: chromatography; flow synthesis; in-line purification; oxadiazole; reaction telescoping

(untitled) - Fitzpatrick, D. E.; Battilocchio, C.; Ley, S. V. (ACS Cent. Sci., 2016)

(untitled) - Wegner, J.; Ceylan, S.; Kirschning, A. (Adv. Synth. Catal., 2012)

(untitled) - Noël, T.; Cao, Y.; Laudadio, G. (Acc. Chem. Res., 2019)

(untitled) - Buglioni, L.; Raymenants, F.; Slattery, A.; Zondag, S. D. A.; Noël, T. (Chem. Rev., 2022)

(untitled) - Baxendale, I. R.; Brocken, L.; Mallia, C. J. (Green Process. Synth., 2013)

(untitled) - Bogdan, A. R.; Dombrowski, A. W. (J. Med. Chem., 2019)

(untitled) - Wegner, J.; Ceylan, S.; Kirschning, A. (Chem. Commun., 2011)

(untitled) - Akwi, F. M.; Watts, P. (Chem. Commun., 2018)

(untitled) - Movsisyan, M.; Delbeke, E. I. P.; Berton, J. K. E. T.; Battilocchio, C.; Ley, S. V.; Stevens, C. V. (Chem. Soc. Rev., 2016)

(untitled) - Ketels, M.; Konrad, D. B.; Karaghiosoff, K.; Trauner, D.; Knochel, P. (Org. Lett., 2017)

(untitled) - Bonner, A.; Loftus, A.; Padgham, A. C.; Baumann, M. (Org. Biomol. Chem., 2021)

(untitled) - Baumann, M.; Moody, T. S.; Smyth, M.; Wharry, S. (Synthesis, 2021)

(untitled) - Newman, S. G.; Jensen, K. F. (Green Chem., 2013)

(untitled) - Brandão, P.; Pineiro, M.; Pinho e Melo, T. M. V. D. (Eur. J. Org. Chem., 2019)

(untitled) - Dallinger, D.; Kappe, C. O. (Curr. Opin. Green Sustainable Chem., 2017)

(untitled) - Donnelly, K.; Baumann, M. (J. Flow Chem., 2021)

(untitled) - Ley, S. V.; Chen, Y.; Robinson, A.; Otter, B.; Godineau, E.; Battilocchio, C. (Org. Process Res. Dev., 2021)

(untitled) - Baumann, M.; Moody, T. S.; Smyth, M.; Wharry, S. (Org. Process Res. Dev., 2020)

(untitled) - Hartman, R. L. (Curr. Opin. Chem. Eng., 2020)

(untitled) - Gioiello, A.; Piccinno, A.; Lozza, A. M.; Cerra, B. (J. Med. Chem., 2020)

(untitled) - Li, Z.; Zhan, P.; Liu, X. (Mini-Rev. Med. Chem., 2011)

(untitled) - Glomb, T.; Szymankiewicz, K.; Świątek, P. (Molecules, 2018)

(untitled) - Wani, M. Y.; Ahmad, A.; Shiekh, R. A.; Al-Ghamdi, K. J.; Sobral, A. J. F. N. (Bioorg. Med. Chem., 2015)

(untitled) - Reichart, B.; Kappe, C. O. (Tetrahedron Lett., 2012)

(untitled) - Green, L.; Livingstone, K.; Bertrand, S.; Peace, S.; Jamieson, C. (Chem. – Eur. J., 2020)

(untitled) - Wong, J. Y. F.; Tobin, J. M.; Vilela, F.; Barker, G. (Chem. – Eur. J., 2019)

(untitled) - Patel, K. D.; Prajapati, S. M.; Panchal, S. N.; Patel, H. D. (Synth. Commun., 2014)

(untitled) - Majji, G.; Rout, S. K.; Guin, S.; Gogoi, A.; Patel, B. K. (RSC Adv., 2014)

(untitled) - Zhang, G.; Yu, Y.; Zhao, Y.; Xie, X.; Ding, C. (Synlett, 2017)

(untitled) - Yadav, A. K.; Yadav, L. D. S. (Tetrahedron Lett., 2014)

(untitled) - Prakash, O.; Kumar, M.; Kumar, R.; Sharma, C.; Aneja, K. R. (Eur. J. Med. Chem., 2010)

(untitled) - Guin, S.; Rout, S. K.; Ghosh, T.; Khatun, N.; Patel, B. K. (RSC Adv., 2012)

(untitled) - Yu, W.; Huang, G.; Zhang, Y.; Liu, H.; Dong, L.; Yu, X.; Li, Y.; Chang, J. (J. Org. Chem., 2013)

(untitled) - Pardeshi, S. P.; Patil, S. S.; Bobade, V. D. (Synth. Commun., 2010)

(untitled) - Donnelly, K.; Baumann, M. (Chem. Commun., 2021)

(untitled) - Weeranoppanant, N.; Adamo, A. (ACS Med. Chem. Lett., 2020)

(untitled) - Thomson, C. G.; Banks, C.; Allen, M.; Barker, G.; Coxon, C. R.; Lee, A.-L.; Vilela, F. (J. Org. Chem., 2021)